Efficacy of a 10% chlorhexidine coating to prevent caries in at-risk community-dwelling adults. (October 2013) - Symington, John M.; Perry, Ross; Kumar, Ashish; Schiff, Robert
Abstract Objective. The purpose of the study was to determine the efficacy of a 10% chlorhexidine tooth coating in reducing the incidence of cavitated carious lesions in adults. Materials and methods. The trial was a randomized, double-blind, multi-center, placebo controlled study with 983 participants, receiving the application of either the active or the placebo coatings to the entire dentition. Four applications were made in the first month and one at the 7th month. The final examination was performed at 13 months. Results. Coronal caries showed a statistical reduction (p = 0.02). Examination of the results by site showed that the highest risk participants experienced the most significant preventive effect (p = 0.003). When two sites (uninsured and public health) are pooled the treatment p-value is 0.0009, interaction term has a p-value of 0.0001. Conclusion. 10% Chlorhexidine was highly effective in high risk participants with more than two cavities at the initial examination. This trial in conjunction with other published trials of this topical medication indicates that chlorhexidine exerts its action by preventing the transition of D1 lesions to cavitated lesions, not on sound to D1 lesions.